La création des chansons chez les Innus : s’exprimer et manifester son existence - Audet, Véronique (Littoral, 2015)

La scène musicale populaire autochtone au Québec. Dynamiques relationnelles et identitaires - Audet, Véronique (Université de Montréal, 2015)

Rufus Wainwright sings "Grey Gardens": on Thomas Mann's "Death in Venice", Tadzio and his pop cultural "life" - Bałżewska, Katarzyna (Beyond Philology: An International Journal of Linguistics, Literary Studies and English Language Teaching, 2015)

Rising Sun: the True Story of Montreal's First International Jazz & Blues Festival - Boicel, Doudou (Doudou Boicel Éditeur, 2015)

A Study of Selected Representative Organ Pieces by Rachel Laurin - Cheng, S.S. (Université du Kansas, 2015)
Over the course of the last decade the organ works of Canadian composer Rachel Laurin (b. 1961) have gained critical acclaim among professional organists. Her organ music has captured the attention of American and Canadian organists, resulting in a series of commissions for new organ works. To date, there are over thirty-two compositions for organ solo. This document explores stylistic issues in Laurin's compositions for solo organ and for organ with other instruments. Pieces that have been selected for in-depth study include Chromatic Fantasietta, Scherzetto, Toccatarina (to Katarina) and Asian Legend from Twelve Short Pieces, Volume 3, op. 64, Étude Héroïque, Op.38, and the Sonata for Organ and Horn, Op.60, II. On a Painting by Thomson. At the outset of the document an overview of Canadian organ culture is provided, followed by an introduction to Laurin's life and works. Subsequently, a structural and harmonic analysis of Laurin's compositions is presented. As this analysis will reveal, the expressive dimensions of her works embrace elements of Romanticism and Impressionism.

Trajet de jeunesse d’une artiste de renommée mondiale. Maureen Forrester, fille de la rue Fabre - Cohalan, Kevin (Bulletin de la Société d’histoire et de généalogie du Plateau-Mont-Royal, 2015)

»Y’a que les très très vieux/ Qui ont encore l’espoir de mourir de vieillesse«. Alter und Apokalypse im französischen Chanson seit der Mitte des 20. Jahrhunderts [La vieillesse et l'apocalypse dans la chanson française depuis le milieu du XXe siècle] - Dietmar, Rieger (KulturPoetik, 2015)
After an introduction to the genre »chanson« and its fascination with real life, this article investigates the different ways in which French (and Franco-Canadian) chansons deal with ageing and old age. The study looks at the songs’ lyrics, which describe or represent old age in a manner between stereotype and intimate confession, and at the authentic or inauthentic performance of the chanson by its singer or singer-songwriter. The analyses are followed by an overview of chansons describing the end of the world. It can be shown that many of these songs focus on the feelings of lovers facing the apocalypse and that in more than one case chansons envisioning the last moments of the world contain a mixture of fear and parody.

La Bolduc. Parlure et accents de ses chansons - Duguay, Sylvie (Éditions Sylvie Duguay, 2015)

The Ethiopian and Eritrean Evangelical Diaspora of Montreal: Music, Identity and Ambivalence - Ferran, Hugo (African Diaspora, 2015)
The Ammanuel Montreal Evangelical Church (amec) is composed of over 150 members of Ethiopian and Eritrean origin. Through the examination of their musical practices, this article analyzes how music is involved in the construction and expression of religious identities in the context of migration. It appears that in borrowing worship music widespread in Ethiopia and in its diaspora, the faithful highlight the "Ethiopianness" of the group, at the expense of the minority Eritrean identity. The author then reveals that each musical parameter conveys different identity facets. If the universality of the Gospel message is expressed through dance and lyrics, the repertoire and its instrumentarium convey the "Ethiopianness" of the congregation, while the rhythms refer to a multi-ethnic Ethiopian imaginary. As for the local identity (Montreal) of the congregation, it is represented by the combination of several hymns borrowed from the stars of Ethiopian Gospel music. Finally, the paper highlights some musical ambivalences of the faithful who, in the context of migration, feel torn between several cultures.

La culture contemporaine du powwow chez les nations autochtones de l’est canadien - Giroux, Dalie (Géographie et cultures, 2015)
Le powwow compte parmi les pratiques culturelles les plus importantes de l’autochtonie nord-américaine, et constitue une pratique artistique en pleine expansion : alors que le powwow existe depuis le XIXe siècle dans le sud-ouest des États-Unis, de nombreuses communautés du sud-est canadien (essentiellement dans les provinces de l’Ontario et du Québec) ont investi cette forme culturelle dans les dernières décennies. L’étude présentée dans ce texte se penche sur ce phénomène des powwows du sud-est canadien, en s’attardant à la fois à la dimension de transferts culturels qui le définit, et à la dimension politique qui y est sous-jacente. Nous nous pencherons pour ce faire sur la définition et les influences autochtones aux origines du powwow contemporain, sur la géographie de ce que les praticiens qualifient de « retour des traditions, et sur la structuration géoculturelle des powwows du sud-est, parmi lesquels nous distinguerons le powwow ojibway (région ontarienne du nord des Grands Lacs), le powwow haudenosaune (péninsule de Niagara et vallée du Saint-Laurent), et le powwow est-algonquien (Outaouais, Haute Mauricie, Lac Saint-Jean).
Keywords: Amérique du Nord; North America; cultures autochtones; dance; danse; indigenous cultures; powwow; territoriality; territorialité

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (1re partie) - Henry, Symon (Circuit, 2015)

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (2e partie) - Henry, Symon (Circuit, 2015)

Sistema in the News: Exploring Media Coverage of Sistema-Inspired Programs in Montreal and Kahnawà:ke - Hopkins, Emily (Université de Montréal, 2015)

Leonard Cohen in the Global Village: Constructions of Identity and Desire in His Poetics - Icíar Álvarez Pérez, María (Université complutense de Madrid, 2015)

Elkahna Talbi : femme de paroles - Lalonde, Catherine (Jeu : revue de théâtre, 2015)

L'esthétique rock queer : de C.R.A.Z.Y. à Xavier Dolan - Laverdière, Gabriel (Nouvelles vues. Revue sur les pratiques et les théories du cinéma au Québec, 2015)
L'analyse proposée des films C.R.A.Z.Y. (Jean-Marc Vallée, 2005), J'ai tué ma mère (Xavier Dolan, 2009), Les amours imaginaires (Dolan, 2010) et Laurence Anyways (Dolan, 2012) convoque trois perspectives : le rock, le camp et le queer. Dans ces films québécois, la musique rock semble orienter la narration et l'esthétique. Elle fait également le pont entre l'anticonformisme auquel renvoie le paradigme rock et l'identité marginale des personnages. L'esthétique de l'image se plie parfois à la bande sonore, qui encourage certains effets visuels. Cela dit, les films de Vallée et de Dolan se servent différemment de l'esthétique rock et du camp, ce qui s'accorde aux représentations distinctes qu'ils produisent eu égard à l'orientation ou à la diversité sexuelles et au genre. L'excès des films de Dolan, leur hyperréférentialité, leur jeu constant entre recherche d'émotions esthétiques et d'émois narratifs, leur fréquente suspension de la réalité contribuent à une écriture du différé dans laquelle les personnages queer jouissent d'une amplitude considérable, alors que dans C.R.A.Z.Y. la performance hyperbolique s'articule plutôt à une analytique de l'homophobie (sociétale et intériorisée) que le film s'efforce de dresser, sans pouvoir échapper à un certain malaise.

Le rap comme activité (s) sociale (s) : dynamiques discursives et genre à Montréal (approche sociolinguistique) - Lesacher, Claire (Université Rennes 2, 2015)
Cette recherche propose d’interroger l’activité rap montréalaise d’un point de vue sociodiscursif et à l’aune du genre, à travers le prisme des pratiques, des représentations, des expériences et des trajectoires de rappeuses à Montréal. Inscrite dans le champ de la sociolinguistique et arrimée aux, ancrages théoriques et épistémologiques qui envisagent le genre comme un rapport social coproduit et les subjectivités en tant que traversées des rapports sociaux, mais jamais Pleinement déterminées par ces derniers, cette étude se base sur une enquête de terrain réalisée en 2011 auprès de rappeuses à Montréal. Axée sur un corpus discursif et interprété selon une méthode qui croise analyse du discours et analyse de contenu thématique, elle engage une approche des phénomènes et des processus à l’œuvre en tant qu’ils sont territorialisés.Les pratiques, les expériences et les représentations des rappeuses seront envisagées dans un contexte marqué par leur « rareté ». Il sera constaté qu’outre une actualisation des rapports sociaux de sexe, les pratiques et les expériences des rappeuses sont aussi impactées par les enjeux sociolinguistiques de l’espace montréalais, ainsi que par ce qui relève du concept de québéquicité. Ainsi, les rappeuses composent leurs pratiques et leurs trajectoires en étant toujours situées à une place unique, dynamique et forcément ambivalente au sein de la matrice de la domination, et qui se façonne notamment par l’imbrication du genre, du langage, des représentations sur le rap, et des héritages d’une idéologie de la francophonie canadienne-française, que réactualise notamment le concept de québéquicité contemporain.

Willie Eckstein, Harry Thomas, Vera Guilaroff: Three Montreal Pianists from the Jazz Age - Litchfield, Jack (Autoédition, 2015)

Musiciens migrants d'origine arabe dans le contexte montréalais : le parcours de la reconnaissance - Marcoux-Gendron, Caroline (Université de Montréal, 2015)

Burgundy Jazz: Little Burgundy and the Story of Montreal Jazz - Marrelli, Nancy (Véhicule Press, 2015)
The area now called Little Burgundy was the birthplace of jazz in Montreal. Explore the textures of Montreal's jazz era through an array of rare jazz artifacts, including swizzle sticks and menus from renowned Montreal nightclubs, flapper dresses of the 1920s, porter uniforms, old LP vinyl records, cocktail shakers, and sheet music. Each object tells a fascinating story!

Mountain City Girls: The McGarrigle Family Album - McGarrigle, Anna; McGarrigle, Jane (Random House Canada, 2015)

Dans un grand champ nu. Des récits, des images, des chants - Miville-Deschênes, Monique (Éditions Trois-Pistoles, 2015)

Vivier reenacted: Singing beyond masculine - Novak, Jelena (New Sound: International Magazine for Music, 2015)
Vivier: A Night Report is a kind of poetical archive of musical details, protocols, experiences, concepts, memories, fears, desires and sorrows connected to Canadian composer Claude Vivier's (1948-1983) unusual destiny. All characters from Marko Nikodijević's opera originate from Vivier's life and works but they are re-indexed, or reenacted differently. The countertenor voice of Vivier is what primarily makes him different from all the rest of the characters. Even it could be claimed that the rest of the voices are dominated by Vivier's vocal presence on stage. Vivier stands as symbol for minority, queer, vulnerable. During his short life he was trying to get his own voice, voice as the personification of freedom and possibility to be heard. Finally he gets vivid, imaginative opera in which both his physical and personified voices are shining by creativity that his art emanate. He gets his singing voice, and he finally gets heard.

Vie musicale à l'église Saint-Viateur-d'Outremont. Victoria Cartier, première grande figure - Panneton, Hélène (Mémoire vivante, 2015)

Queering Discourses of Urban Decline: Representing Montréal's Post-World War II "Lower Main" - Podmore, Julie (Historical Geography, 2015)
In this paper, I examine how urban redevelopment and the regulation of public spaces in Montréal in the 1960s transformed the representations of the Lower Main, the city’s historic red-light and entertainment district. I argue that although the Lower Main had long been central to anti-urban discourses regarding heterosexual prostitution, by the 1960s the increased regulation of the city’s queer and trans populations changed its meaning as a representation of the inner city in decline. A central objective is to use this case study to queer discourses of urban decline by considering how heteronormativity was involved in the construction of the city’s sexual margins in the post-World War II period. A related objective is to call into question the narrative of “decline” itself by providing one example of the opportunities it created for queer place-making.

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

Pop Stars as Ambassadors of Sephardic Culture at the Festival Sefarad in Montreal - Roda, Jessica (Contemporary Jewry, 2015)
On their arrival in Montreal, Moroccan Jews established themselves as a community and created a festival in order to promote, gain recognition of, and institutionalize their culture and identity into the broader Jewish community of Montreal. In this article, I propose to analyse the festival as a “thing” (Kopytoff 1986), the biography of which will give us information about its transformation, in terms of representation, through time. From ethnography and historical analysis of the festival, as well as an examination of cultural policies in Canada, Quebec and Montreal during the last decades, we will discover that Sephardic musical heritage, which was initially used for community celebration, was progressively transformed into a marketable product embodied by international pop stars. The representation of Sephardic identity transitioned from a specific cultural reference to Morocco, to Judeo-Spanish and Judeo-Arabic songs, to a plethora of references promoted by Sephardic pop stars, mainly from France and Israel. More broadly, this study will illuminate issues surrounding strategies implemented by the community leaders to be part of these cultural policies and gain visibility in the public sphere.
Keywords: Festival; Montreal; Morocco; Representation; Sephardic; Stars

Les chemins de ma liberté - Simard, Nathalie (Éditions des Intouchables, 2015)

Java to Jazz: Eva Gauthier - Spiller, Henry (Javaphilia: American Love Affairs with Javanese Music and Dance, 2015)

Marketing, Merch, and Media: Nicole Lizée, in Conversation - Wiseman, Howard; Disman, Adriana (Canadian Theatre Review, 2015)
Nicole Lizée is an award-winning classical music composer and performer who composes for string quartet, electronic music, turntable, film, and other media. She has emerged as a major new voice in new classical composition, winning the coveted Canada Council for the Arts Jules Léger Prize (2013) for new Canadian chamber music with her work White Label Experiment. She has been commissioned by the Kronos Quartet among many other prestigious ensembles. This interview engages her relation to various aspects of her work, from marketing and promotion to inspiration and creation in the context of “avant garde” music. How can marketing continue to be part of the art itself? Does instinctively not fitting into a box allow for greater freedom to explore classical and chamber music in the broader context of film and other media? What other factors may be contributing to the inspired vitality of her work?
Keywords: Entretien